A systematic review of the association between health literacy and pain self-management. Issue 6 (June 2022) - Kim, Kyounghae; Yang, Yuxuan; Wang, Zequan; Chen, Jie; Barandouzi, Zahra A.; Hong, Hyejeong; Han, Hae-Ra; Starkweather, Angela
Abstract: Objective: To synthesize the impact of health literacy on pain self-management contexts, processes, and outcomes. Methods: This systematic review employed a narrative synthesis. We used databases, including PubMed and PsycINFO, and handsearching of the reference lists to identify articles published before December 2020. Pain self-management variables were chosen based on the Individual and Family Self-Management Theory. Quality was assessed using the National Institute of Health quality assessment tool for observational and cross-sectional studies. Results: Twenty studies that included 6173 participants were used. Most studies measured functional domains of the health literacy concept. Twelve studies reported small to large associations between health literacy and pain knowledge, medication regimen adherence, or pain. Thirteen studies considered health literacy clinical risks in tailoring education, while seven viewed it as personal assets developed via education. Conclusions: Limited information on the contribution of health literacy to pain self-management context factors and processes exists. Current evidence was limited by a lack of temporality, theoretical basis, and a priori sample estimation. Practice Implications: Using brief functional literacy scales in the clinical environment can be more practical. Identifying patients' literacy levels helps clinicians personalize education, which then promotes patients' knowledge of pain, medication regimen adherence, and pain control. Highlights: Functional literacy was related to pain and medication knowledge and pain. Limited evidence existed on links from literacy to pain-specific contextual factors. Most studies used either objective or perception-based tools of functional literacy. Low functional literacy was considered as risks requiring tailored health education.